Wheat Bran Substitution and Different Soaking Time on Chemical and Organoleptic Quality Chocolate Chip Cookies - Gabriele Nathania Poentoadji; Fadjar Kurnia Hartati (CV. Media Digital Publikasi Indonesia, 2023)
Cookies are a popular snack enjoyed by many people. One of the favored cookie types is chocolate chip cookies. Cookies are made from flour, eggs, fat, sugar, water, and salt. Wheat flour itself is made from wheat which has high fiber. The addition of wheat bran in making cookies is considered to be a good source of fiber. So, cookies can be a healthy food. This study aimed to determine the substitution concentration and soaking time on the chemical and organoleptic quality of chocolate chip cookies. The research used a randomized block design with 2 different wheat bran flour concentrations and soaking times of 5, 10, and 25 minutes each. The results showed that the soaking time had no significant effect on the crude fiber content and water content of chocolate chip cookies, but had a very significant effect on the protein content. An organoleptic test based on Friedman showed that the substitution of wheat bran flour and different soaking times significantly affected the parameters of taste, aroma, and mouthfeel. The best treatment was chocolate chip cookies with 25 grams of wheat bran flour substitution and 5 minutes of soaking time with the highest Yield Value (NH) of 0.45 with the criteria of protein content 5.650%, water content 2.352%, crude fiber content 3.287%, taste 4, 09 (like), aroma 3.63 (rather like), mouthfeel 3.44 (rather like).